2020
DOI: 10.3390/jcm9051330
|View full text |Cite
|
Sign up to set email alerts
|

Shape and Enhancement Analysis as a Useful Tool for the Presentation of Blood Hemodynamic Properties in the Area of Aortic Dissection

Abstract: The aim of this study was to create a mathematical approach for blood hemodynamic description with the use of brightness analysis. Medical data was collected from three male patients aged from 45 to 65 years with acute type IIIb aortic dissection that started proximal to the left subclavian artery and involved the renal arteries. For the recognition of wall dissection areas Digital Imaging and Communications in Medicine (DICOM) data were applied. The distance from descending aorta to the diaphragm was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…Contrast was included in the radiological diagnosis. As the total concentration of contrast (Visipaque) during one AngioCT analysis was constant (1.5 mL per 1 kg of body weight) in the aorta, we focused only on the distribution of brightness in whole domain for the aorta’s reconstruction [ 27 ]. Medical data was retrospectively collected after obtaining written informed consent to participate in the study and were anonymized before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Contrast was included in the radiological diagnosis. As the total concentration of contrast (Visipaque) during one AngioCT analysis was constant (1.5 mL per 1 kg of body weight) in the aorta, we focused only on the distribution of brightness in whole domain for the aorta’s reconstruction [ 27 ]. Medical data was retrospectively collected after obtaining written informed consent to participate in the study and were anonymized before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Despite optimal medical management, a subset of these patients will develop aneurysmal degeneration [11]. Our previous results showed that each time a connection of the true and false duct appeared, the true duct had lower brightness compared to the common duct and false duct, and the false duct was characterized by higher brightness [19]. Current results indicated that the parameters derived from CFD simulations on patient-specific aortic dissection geometries strongly correlate to medical data derived from such patients.…”
Section: Discussionmentioning
confidence: 69%
“…It was noticed that each time a connection of the true and false duct appeared, the true duct had lower brightness compared to the common duct and false duct. Also, false duct was characterized by higher brightness if compared to common duct [19]. Therefore, the aim of the study was to prepare a CFD model of chosen blood flow parameters within the aorta and aortic branches in patients with type B aortic dissection before and after a thoracic endovascular aortic repair procedure.…”
Section: Introductionmentioning
confidence: 99%
“…CFD simulations based on patient-specific models may provide insight into the biomechanical behavior of blood flow, allowing quantitative analysis of hemodynamic patterns, and predicting clinical progression. However, its clinical value still requires verification [22]. Depending on the type of problem analyzed, blood maybe reconstructed as Newtonian or non-Newtonian [23].…”
Section: Introductionmentioning
confidence: 99%